Prediction of multi-parameters in the inverse heat conduction problems. (November 2020) - Abdelhamid, Talaat; Chen, Rongliang; Alam, Mahbub
Abstract: This paper studies the prediction of the spatial-dependent-heat transfer coefficient γ ( x ) and- heat flux q ( x ), using the modified conjugate gradient method (MCGM). The mathematical formulation of the problem well defined and the existence of the minimizer is investigated. We establish the sensitivity and adjoint equations for computing the gradient with respect to γ ( x ) and q ( x ). The proposed algorithm 4.1 is derived for reconstructing γ ( x ) and q ( x ) using the MCGM. The numerical experiments are examined to show the efficiency and accuracy of the proposed method. Finally, some conclusions and remarks are given.